PENGEMBANGAN MEDIA POP UP BOOK METAMORFOSIS HEWAN PADA PEMBELAJARAN IPAS UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA KELAS IV SD - Kezia Supraba, Gones; Winanto, Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to develop Pop Up Book media on animal metamorphosis in IPAS learning that is feasible and effective to increase students' interest and learning outcomes. This research uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). This Pop Up Book learning media has gone through several stages of testing, such as product validity tests, feasibility tests, and media effectiveness tests. The subjects of this study amounted to 26 fourth grade students. This study shows the results of validation testing by media experts with an average percentage of 98% and the results of validation testing by material experts with an average of 93%, so that the results of media and material expert validation testing are categorized as feasible, not revised. The results of the average pre test of 65 and the average post test of 76.5 show an increase as well as the results of the average percentage of interest questionnaires before treatment 67% and for the percentage of interest questionnaires after treatment 79%. So it can be said that this Pop Up Book media is feasible and effective to use for learning.